1997
DOI: 10.1111/j.2042-3306.1997.tb05084.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and possible biological roles of progestagens during equine pregnancy and in the newborn foal

Abstract: Summary Major progress on the endocrinology of the pregnant mare has been possible thanks to the catheterised equine fetal preparation developed by Marian Silver. In particular, these preparations led to the identification of the source of progestagens within the feto‐placental unit and provided the impetus for further work on their biosynthesis and biological activities. The biosynthesis of the progestagens involves close interaction between the fetus, the endometrium and the placenta, and gives rise to some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
6

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 36 publications
1
23
0
6
Order By: Relevance
“…synthesize significant quantities of pregnenolone. Chavatte et al [137,138] found that adrenals from mid-to-late gestation fetuses exhibited little or no capacity to use cholesterol for steroid synthesis when compared with adrenal tissue from foals, concluding that "the 5a-pregnanes found in fetal blood in late gestation do not originate from the adrenal" [138]. Han et al [139] noted relatively few cells in the equine fetal adrenal cortex expressing cytochrome P450 cholesterol side-chain cleavage, the enzyme directly responsible for pregnenolone synthesis.…”
Section: The Feto-placental Unitmentioning
confidence: 95%
“…synthesize significant quantities of pregnenolone. Chavatte et al [137,138] found that adrenals from mid-to-late gestation fetuses exhibited little or no capacity to use cholesterol for steroid synthesis when compared with adrenal tissue from foals, concluding that "the 5a-pregnanes found in fetal blood in late gestation do not originate from the adrenal" [138]. Han et al [139] noted relatively few cells in the equine fetal adrenal cortex expressing cytochrome P450 cholesterol side-chain cleavage, the enzyme directly responsible for pregnenolone synthesis.…”
Section: The Feto-placental Unitmentioning
confidence: 95%
“…The fetal HPA axis may have a role in controlling the length of gestation in the mare through adrenal production of pregnenolone, P 5 (Silver 1994; Chavatte et al . 1997; Ousey 2004; Fowden et al .…”
Section: The Hypothalmic‐pituitary‐adrenal Axismentioning
confidence: 99%
“…2008). This steroid is believed to be the main precursor for uteroplacental production of the progestagens that control uterine quiescence during the second half of equine pregnancy (Silver 1994; Chavatte et al . 1997; Ousey et al .…”
Section: The Hypothalmic‐pituitary‐adrenal Axismentioning
confidence: 99%
“…Most 5 α‐DHP is then returned to the foetus and further metabolized into other progestins, while some (30%) is excreted into the maternal circulation along with other progestins (Hamon et al. 1991; Chavatte et al. 1997; Ousey et al.…”
Section: Endocrinologymentioning
confidence: 99%